Iodine-Induced Hyperthyroidism—An Old Clinical Entity That Is Still Relevant to Daily ICU Practice: A Case Report - E. Brotfain; L. Koyfman; A. Frenkel; A. Smolikov; A. Zlotnik; M. Klein (Case Reports in Endocrinology)
Objective. Hyperthyroidism has been described as elevated serum free T3 and/or free T4 levels with decreased thyrotropin (TSH) concentrations. The main causes are related to autoimmune and neoplastic pathology. However, it might be caused due to a long-term topical exposure (iodine solution dressing) or by intravenous administration of iodine-containing substances. Both clinical and laboratory features might be presented. The main management is based on interruption of all exposures with iodine solutions and also antithyroid medicine in case of severe laboratory and clinical disturbances. Data Sources. We present a case of iodine-induced hyperthyroidism in a critically ill ICU patient caused by excessive iodine containing antiseptic solution washes and contrast agent administration. The patient was successfully treated by discontinuing iodine exposure and beta-blocker administration. Conclusions. In patients with underlying thyroid gland pathology, thyroid-function tests and clinical observation in the ICU are of critical importance.